A new name for the single species of Nohawilliamsia and corrections in Gomesa (Orchidaceae) - Chase, Mark W. (Phytotaxa, 2009)
Nohawilliamsia, with the single species, N. orthostates, was recently published but the specific designation of this species as the type was omitted, thus making the new names invalidly published. This error and a few other small ones in the transfers of species of Oncidium to Gomesa are corrected.